Does Truth Win When Teams Reason Strategically? - Jeannette Brosig-Koch; Timo Heinrich; Christoph Helbach (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This study tests experimentally whether teams can create synergies in strategic interactions. For our comparison between team and individual behavior we employ the race game. This game has the advantage that the optimal strategy does neither depend on beliefs about other players nor on distributional or efficiency concerns. Our results reveal that teams do not only outperform individuals but that they can also beat the 'truth-wins' benchmark. In particular, varying the length of the race game we find that the team advantage increases with the complexity of the game. The latter finding supports the conjectures made by Charness et al. (2010) and Cooper and Kagel (2005), who suggest a relation between task complexity and the size of synergies created by teams. – – Diese Studie untersucht experimentell, inwiefern Teams in strategischen Interaktionen in der Lage sind, Synergien zu erzeugen. Hierzu spielen Individuen und Teams das Race Game, in dem die optimale Strategie sowohl von den Erwartungen bzgl. des Verhaltens der anderen Spieler als auch von den Präferenzen bezüglich der Verteilung oder der Effizienz des Ergebnisses unabhängig ist. Die Daten zeigen, dass Teams im Race Game besser abschneiden als Individuen und sogar den Truth-Wins Benchmark übertreffen können. Es zeigt sich insbesondere, dass der Vorteil der Teams mit steigender Komplexität der Spiele zunimmt. Dieses Ergebnis unterstützt die These von Charness et al. (2010) und Cooper und Kagel (2005), die einen Zusammenhang zwischen der Komplexität einer Aufgabe und möglichen Synergien in Teams vermuten.
Keywords: C72; C91; C92; 330; race game; strategic sophistication; team decision making